Analisis Estetika pada Karya Seni Patung Dolorosa Sinaga - Patriansah, Mukhsin (UNIVERSITAS INDO GLOBAL MANDIRI)
The work of art is a visual form that always communicates and even expresses the ideas and experiences that the birth of his sisenimannya. The artwork that is present is a representation of the phenomena that exist in the environment that has a certain meaning and meaning to dissected and analyzed. In addition, artwork is a visual form that always communicates and even expresses ideas and experiences that are born by the sisenimannya. The artwork that is present is a representation of the phenomena that exist in the environment that has a certain meaning and meaning to dissected and analyzed. Analyzing a work of art seems unfair if we do not specify the cultural context of the time in which the work of art was born. Dolorosa Sinaga is a woman born in the tribe of Batak. Batak itself has Patrilineal kinship system. in the Patrilineal community structure based on the father lineage (male), the descendant of the father (male) is considered to have a higher position and his rights will also get more. This brief explanation of the artist's background has become a reference to be developed in interpreting the work analyzed later. Meanings and messages to be conveyed visible from the figure of a mother who was carrying her child. Mothers are women who do not get the highest place among the Batak tribe, so the inheritance belongs entirely to men. The suffering of women is illustrated by the expression of a mother on this work that suffers with an open mouth. Open mouth is part of the complexity of this work because it has the meaning and meaning of a mother who wants to ask for help when a mother is left by the men.